INTERFAITH DIALOGUE AND PEACEBUILDING: LESSONS FROM ISLAMIC TRADITIONS - Retna Dwi Estuningtyas (Penelitian dan Pengembangan Ilmu, 2024)
Interfaith dialogue plays an important role in peacebuilding, but the practices and values ​​in Islamic teachings that can support this dialogue remain underexplored. This research aims to identify relevant Islamic practices and values ​​that can be integrated into interreligious dialogue programs in countries experiencing conflict. Through a systematic review of existing literature, this research finds that the principles of justice, compassion, and the obligation to dialogue can be implemented effectively to increase collaboration between communities, thus making a significant contribution to peacebuilding efforts.